Pengaruh Event Marketing, Content Marketing, Influencer dan Lingkungan Sosial Terhadap Keputusan Pembelian Skin Mobile Legends - Ajizah Himawati; Dewi Noor Susanti (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
Games that were initially enjoyed individually and offline have now evolved into online games that allow interaction, competition, and friendship with other players in real-time. Online games are now increasingly popular, one of which is Mobile Legends. This game can be downloaded through the Play Store and App Store. In April 2024, Mobile Legends ranked the most popular game by downloads on the statista.com website. The research objective was to determine the influence of event marketing, content marketing, influencers, and the social environment on the decision to purchase Mobile Legends game skins in Kebumen Regency. The method used was non-probability sampling with a purposive sampling technique aimed at 100 users. Data collection techniques used questionnaires and literature studies. The data analysis technique used multiple linear regression, which was then processed with the SPSS application version 25.0 for Windows. The results showed that event marketing had a significant effect on purchasing decisions, content marketing had a significant effect on purchasing decisions, influencers had no significant effect on purchasing decisions, the social environment had no significant effect on purchasing decisions, and event marketing, content marketing, influencers, and the social environment simultaneously had a significant effect on purchasing decisions.